2014
DOI: 10.1590/0001-3765201420130507
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant capacity of tea of Echinodorus grandiforus, “leather hat,” in Wistar rat liver

Abstract: Oxidative stress has been considered as one of the factors responsible for hepatic diseases, which sometimes require new ways of treatment. The present study aimed to evaluate the in vitro antioxidant capacity of the tea of Echinodorus grandiforus ("leather hat" plant) in rat liver. Different preparations of tea were evaluated for phenolic composition, antioxidant activity by DPPH assay and ability to inhibit lipid peroxidation induced by copper sulfate. The antioxidant activity was assessed in liver tissue tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
1
1
0
1
Order By: Relevance
“…It is well documented that isoorientin (Lunagariya et al, 2014) and isovitexin inhibit lipase activity, which justifies the pancreatic lipase inhibitory activity of E. grandiflorus EtOH extract. In addition, our results corroborate another study that showed that the tea from E. grandiflorus has anti-oxidant capacity (Lunardi et al, 2014).…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is well documented that isoorientin (Lunagariya et al, 2014) and isovitexin inhibit lipase activity, which justifies the pancreatic lipase inhibitory activity of E. grandiflorus EtOH extract. In addition, our results corroborate another study that showed that the tea from E. grandiflorus has anti-oxidant capacity (Lunardi et al, 2014).…”
Section: Introductionsupporting
confidence: 91%
“…The ethanolic extracts of C. sinensis, R. officinalis leaves and aqueous extract of E. grandiflorus leaves have also been reported to decrease hyperglycemia, oxidative stress, lipid peroxidation and activate antioxidant enzymes (Alonso-Castro et al, 2012;Haidari et al, 2013;Lunardi et al, 2014). A previous study also showed that M. charantia leaves control postprandial hyperglycemia and glucose tolerance, and its methanolic ex-tract presents free radical-scavenging properties and inhibitory activity against nitric oxide production (Tsai et al, 2014).…”
Section: Figuramentioning
confidence: 99%
See 1 more Smart Citation